A creep model coupling moisture and mechanical damage for water-bearing concrete. (4th April 2022) - Zheng, Zhao-Qiang; Liu, Huai-Zhong; Xiao, Ming-Li; He, Jiang-Da; Xie, Hong-Qiang; Zhuo, Li
Highlights: A concrete creep model coupling moisture and mechanical weakening effect was proposed. The model can represent the entire creep behavior for water-bearing concrete. Damage on both short-term and long-term Mohr–Coulomb strength parameters are linear to moisture content. Moisture-induced damage is found to be time independent. Abstract: The influence of moisture content and overstress on the creep of concrete was investigated from the perspective of damage rheology theory. The weakening effects of moisture and overstress were characterized by a time-independent and a time-dependent damage functions, respectively, and then combined and applied to a modified creep model that can represent the elasto-visco-plastic creep deformation of concrete. Hence, a damage creep model is proposed to describe the creep behavior of water-bearing concrete. Theoretical and statistical analyses, as well as a comparison with the ACI-209 model were performed to examine the validity and superiority of the proposed model. Further analyses showed that not only the deformation parameters, but also the long-term strength parameters degraded with time and increasing moisture. Experiments were then conducted on saturated cement mortar with different static moisture holding durations to investigate the time correlation of moisture-induced damage on the mechanical properties of the material. The experimental results proved that moisture-induced damage was independent of time.